Linguo-pragmatic potential of Persian omens and superstitions: DOI: https://doi.org/10.17721/1728-242X.2020.26.31-36 (BULLETIN OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV. ORIENTAL LANGUAGES AND LITERATURES, 2023)
This paper attempts to find out the linguo-pragmatic potential of Persian folk omens and superstitions according to their reasonableness / unreasonableness for the individual and the functions they perform in daily lives of Iranians. The views of national and foreign scholars on the problem of folk omens and superstitions studying and systematizing, the reasons and consequences of the functioning of these linguistic and cultural units in human communities are briefly characterized; classifications proposed by researchers are examined. Some scholars consider fear as a reason of human belief in omens and superstitions, as well as trying to explain environmental phenomena that go beyond everyday experience and do not fit the usual imagination. There is no doubt that beliefs compiling these microtexts have come from ancient times, but despite their specific, often illogical nature, they are so ingrained in the minds of people that continue to function in contemporary communities as peculiar cultural constants and prescriptions regulating everyday human behavior. Scholars point out objective and non-objective folk omens and superstitions. Objective or true omens are based on centuries-old experience and observations of generations, they have a logical explanation, and therefore it is useful to imitate them. Non-objective or false superstitions reflect unrealistic, non-existent links between phenomena, man and nature, they are false and fictitious. The paper outlines some peculiarities of reasonable and unreasonable Persian signs and superstitions functioning in comparison with the Ukrainian ones in the respective linguistic and cultural communities. These microtexts have been found to perform a number of functions in a person's daily activities, including regulatory, prognostic, axiological, moral, ethical, psychotherapeutic, and other functions. It is concluded that the study of folk omens and superstitions through the spectacle of linguo-pragmatics opens the way to a better understanding of the processes of comprehension of the surrounding reality by representatives of a certain linguistic culture, that are always characterized by vivid ethno-specificity.
Keywords: linguo-pragmatics; folk omen; superstition; linguistic culture